2021
DOI: 10.3390/en14196336
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the CO2 Emissions at the Global Level: A Multilayer Artificial Neural Network Modelling

Abstract: Better accuracy in short-term forecasting is required for intermediate planning for the national target to reduce CO2 emissions. High stake climate change conventions need accurate predictions of the future emission growth path of the participating countries to make informed decisions. The current study forecasts the CO2 emissions of the 17 key emitting countries. Unlike previous studies where linear statistical modeling is used to forecast the emissions, we develop a multilayer artificial neural network model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The results showed that the countries with high emissions such as China, India, Iran, Indonesia, Saudi Arabia would reach higher values in the near future and the countries with low emission levels such as Mexico, South Africa, Turkey and South Korea would follow an increasing trend, while the emiisions in countries such as America, Japan, England, France, Italy, Australia and Canada would decrease. In addition, the study highlighted that that such forecasts could guide the countries in the transition process to the green economy (Jena et al, 2021).…”
Section: Jena Et Al (2021) Carried Out Their Work On Carbon Emission ...mentioning
confidence: 99%
“…The results showed that the countries with high emissions such as China, India, Iran, Indonesia, Saudi Arabia would reach higher values in the near future and the countries with low emission levels such as Mexico, South Africa, Turkey and South Korea would follow an increasing trend, while the emiisions in countries such as America, Japan, England, France, Italy, Australia and Canada would decrease. In addition, the study highlighted that that such forecasts could guide the countries in the transition process to the green economy (Jena et al, 2021).…”
Section: Jena Et Al (2021) Carried Out Their Work On Carbon Emission ...mentioning
confidence: 99%
“…The literature on climate change, gas emissions of nations, and equity is voluminous. Some of the most significant contributions are those made by Sagar [31], who studied the allocation scheme of emissions; Vaillancourt and Waaub [32], who developed a model to allocate emissions based on the equity principle; Markandya [33], who conducted an analysis of the distribution of climate change; Mattoo and Subramanian [34], who conducted a review about equity and climate change; Remuzgo et al [35], who studied the evolution of GHG emissions during 1990-2011; Alcaraz et al, who developed a model of climate justice per capita [36] and applied it to the Mediterranean [37]; and Jena et al [38], who designed a nonlinear model to forecast the CO 2 emissions of the 17 key emitting countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that using an optimization algorithm to minimize the error affects the exactness of the predicted values. Jena et al [16] used multilayer ANN to forecast CO 2 emission of 17 countries that had a key role in the worldwide emission and observed an average of 96% forecasting accuracy, which was much more than the previous models.…”
Section: Introductionmentioning
confidence: 99%